Introducing phonology - Odden, David Arnold, 1954- (Cambridge : Cambridge University Press, 2013)
'Designed for students with only a basic knowledge of linguistics, this leading textbook provides a clear and practical introduction to phonology, the study of sound patterns in language. It teaches in a step-by-step fashion the logical techniques of phonological analysis and the fundamental theories that underpin it. This thoroughly revised and updated edition teaches students how to analyze phonological data, how to think critically about data, how to formulate rules and hypotheses, and how to test them. New to this edition: [bullet] Improved examples, over 60 exercises and 14 new problem sets from a wide variety of languages encourage students to practise their own analysis of phonological processes and patterns [bullet] A new and updated reference list of phonetic symbols and an updated transcription system, making data more accessible to students [bullet] Additional online material includes pedagogical suggestions and password-protected answer keys for instructors'--
Includes bibliographical references and index.
Buku bacaan asas fakulti
Keywords: Grammar, Comparative and general -- phonology